2005
DOI: 10.1016/j.ijdevneu.2005.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Heat stress induced histopathology and pathophysiology of the central nervous system

Abstract: The number of reports on the effects of heat stress is still increasing on account of the temperature is one of the most encountered stressful factors on the different biological systems. Because the heat stress (HS) considered a model of thermal injury to the central nervous system (CNS), the purpose of this review was to assess the histopathological changes of HS on CNS. Also, this review emphasized that the heat stress may retard partially the degree of the postnatal neurogenesis and growth of CNS. Taken to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 100 publications
(131 reference statements)
0
11
0
Order By: Relevance
“…Likewise, restricting memory-based tasks and experiences reduces hippocampal volume and neurogenesis in a passerine bird (LaDage et al, 2009(LaDage et al, , 2010. Alternatively, disruption of central nervous system (CNS) development by environmental stress exposure (nutritive, chemical, electromagnetic and thermal) has been shown in every model system studied to date, including humans (Ahmed, 2005;Rice and Barone, 2000;Roebuck et al, 1998;Weinstock, 2001). For example, neural tube defects, one of the most common birth defects of the CNS in humans, have been linked to hyperthermia during early pregnancy (Chambers, 2006;Chan et al, 2014;Dreier et al, 2014;Moretti et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, restricting memory-based tasks and experiences reduces hippocampal volume and neurogenesis in a passerine bird (LaDage et al, 2009(LaDage et al, , 2010. Alternatively, disruption of central nervous system (CNS) development by environmental stress exposure (nutritive, chemical, electromagnetic and thermal) has been shown in every model system studied to date, including humans (Ahmed, 2005;Rice and Barone, 2000;Roebuck et al, 1998;Weinstock, 2001). For example, neural tube defects, one of the most common birth defects of the CNS in humans, have been linked to hyperthermia during early pregnancy (Chambers, 2006;Chan et al, 2014;Dreier et al, 2014;Moretti et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Research over the past decade has demonstrated that hyperthermia causes various damages to the animal body, including injuries in the central nervous system [1] and adrenal glands [2], reduction of thyroid physiology in lactating cows [3], and gastrointestinal hyperpermeability [4]. The integrity (both structural and functional) of the small intestine is essential for absorption of nutrients.…”
Section: Introductionmentioning
confidence: 99%
“…20 Hsp72 overexpression in multiple vital organs including the heart and the brain has been demonstrated to confer protection against heatstrokeinduced hyperthermia, circulatory shock, and cerebral ischemic injury in rats and mice. [40][41][42][43] On the other hand, circulating Hsp72 levels have been suggested to be a candidate marker of the extent of tissue damage and necrotic cell death during heatstroke. 44 A possible mechanism by which Hsp70 protects against heatstroke-induced hemodynamic dysfunctions may involve the potentiation of baroreceptor reflex response through its expression in the nucleus tractus solitarii, the principal recipient of baroreceptor afferent fibers in the medulla oblongata.…”
Section: Role Of Hsps In Heat Adaptation and Protection Against Heatsmentioning
confidence: 99%